Verbal abuse of nurses by physicians in a private sector setting - E Joubert; A du Rand; N van Wyk (AOSIS, 2005)
The aim of the study was to determine whether physicians in a private sector setting verbally abuse nurses, and to what extent. A review of the literature showed that verbal abuse by physicians accounts for the highest incidence of aggression towards nurses in health care, and that it is strongly related to turnover rates. It has also been reported in recent studies that within the context of verbally abusive episodes, patient care, work productivity, morale and job satisfaction have been negatively affected. Of the 120 questionnaires that were distributed among registered and enrolled nurses, 83 were returned in time to be used, which was a response rate of 69%. This response rate is consistent with previous studies and is exactly the same as for a study that was done in Turkey (Uzun, 2003:81). The questionnaire used was one that has been adapted from the Verbal Abuse Scale developed by Manderino and Berkey (1997:50) and the Revised Conflict Tactics Scale (CTS 2) as described by Little (1999:24), and was in the form of a 4-point Likert-scale with one open ended question. The results showed that 79% of the nurses admitted that verbal abuse was taking place. Forms of direct verbal abuse included 81 % that felt they were criticised unjustly, 76% that were screamed at in front of others, and 81 % that felt physicians vented their frustration on them. The results obtained in the study were consistent with previous studies done elsewhere and it indicated that nurses still experience high levels of verbal abuse in the workplace.